Estudo metabolômico dos constituintes voláteis de algodoeiro submetido à interações bióticas e abióticas e mecanismos de indução de resistência - Aquino, Flávia Rego de (2020)
Plants have developed several defense strategies against herbivory, one of which is the response of induced defenses that represents the biosynthesis of phytotoxic molecules through attack. Plant resistance mechanisms can be classified according to its interactions with the insect pest as resistance to antibiosis and non-preference. The emission of volatile organic compounds has been studied as one of the communication mechanisms between plants and plants and, also, as a defense response to herbivory. The study of the volatile components of cotton (Gossypium hirsutum) submitted to biotic interactions (herbivory by Spodoptera cosmioides) and abiotic interactions (methyl-jasmonate, α-pinene and water stress) is showed as a strategy in this work to search for knowledge of the response mechanisms. It can be able to collaborate with new proposals and policies for sustainable agricultural management of insect pest control. For this, the volatile metabolomic profile of cotton plants submitted to different biotic and abiotic stresses were evaluated by chromatographic and spectrometric techniques (HS-GC-MS) in comparison with behavioral data from the model insect. It was observed the marked production of the volatile compounds Hexanal, 2-Hexenal, α-Pinene, β-Pinene, β-Mircene, Limonene and Caryophylene after resistance induction, as well as the decrease in the production of β-Ocimene. These results indicate the activation of two main routes for resistance induction: formation of volatile compounds from fresh leaves from the oxidation of the plant membrane, which generate the biosynthesis DE NOVO volatile organic compounds, and the Heliocides biosynthesis route, which act to decrease palatability. of the leaves. The chemical profile of plants with induced resistance was able to significantly repel the action of the Spodoptera cosmioides caterpillar. It was showed, then, that these strategies have great potential for sustainable agricultural management, in addition to providing information that contributes to the knowledge of insect-plant interactions.